Plasma and intracellular (platelet) zinc levels in chronic renal failure (CRF) patients under different treatment modalities - Khalil, O A; Mostafa, E; Zanaty, M A F; Omar, H M (African Journal of Nephrology, 2016)
The causes and degree of zinc (Zn) deficiency in uraemia are still controversial. The effect of different treatment modalities are still unsettled. Plasma Zn represents only a small part of the total body Zn (about 0.5%). Thus determination of intracellular Zn in the peripheral blood cells might be more reliable. The present study was designed to assess the actual Zn status in uraemia and to find whether the treatment modalities of CRF (conservative and dialytic) could influence Zn status. Also to determine the elfeet of single dialysis session, type of dialysis and dialysate buffer on the Zn status. This study included ten healthy controls and fourty CRF patients divided in three subgroups on different treatment modalities (10 conservative treatment, 15 on intermittent perioneal dialysis ((IPD) and 15 on haemedialysis (HD). Zinc was measured by atomic absorption spectrophotometry in plasma and platelets. Statistically significant decrease of plasma Zn and significant increase of platelet Zn were found in CRF patients on different treatment modalities as compared to controls (P<0.01), but there was no significant difference in this respect hetween the three uraemic subgroups. There was no difference as regard serum protein and albunun levels in uraemic subgroups compared to controls. Moreover plasma Zn was significantly increased (still less than control) and platelet Zn was significantly decreased (P<0.01) after a single dialysis session in both IPD and HD subgroups, but the changes of both parameters (before and after dialysis) were insignificant in IPD patients compared to HD patients. Significant negative correlation was found between platelet Zn and creatinine clearance in the three uraemic subgroups (r = -0.81 P<0.01 in conservative patients, r= -0.72 P<0.01 in IPD and r= -0.76 P<0.01 in HD) while no correlation could be detected between the duration of dialysis and each of platelet & plasma Zn and between plasma Zn and each of platelet Zn, serum creatinine and clearance. Plasma Zn showed transient significant rise in HD patients using bicarbonate (11.6 ± 1.1 umol/L) as compared to those using acetate buffer (9.1 ± 1.3 umol/L), P<0.01. We can conclude that intracellular measurements of Zn (platelet) is of value in diagnosis and monitoring of Zn status in uraemics. Different treatment modalities does not influence Zn haernostasis. with no superiority of particular type of dialysis in this respect. The effect of a single dialysis session and the use of bicarbonate versus acetate buffer was just a transient rise of plasma Zn due to haemoconcentration and better correction of acidosis during dialysis.